PUBLIC OR PRIVATE WORK ENVIRONMENT? A COMPARATIVE STUDY ON THE USE OF ENGLISH PHRASES IN EVERYDAY COMMUNICATION (PANGEEA, 2025)
ABSTRACT: The effects caused by the influence of the English language on the communication in the Romanian language, the terminological diversity introduced in the language in the last period, the speed with which this influence imposes itself on the level of the Romanian language, as well as the important changes that the communication in the Romanian language undergoes, are some of the reasons that led us to dwell on this subject. The main aspects that favored the borrowings from the English language, the favorable context for the penetration of foreign elements into our language, as well as the current situation of the Romanian language, after the penetration and even the spread of words and expressions of English origin, are aspects presented in the work. At the same time, a particularly important aspect is the comparison between the motivation of public and private employees regarding the degree of openness towards the adoption, integration and use of terms of English origin, so we consider it important to highlight the different reasons why public and private employees opt for words of English origin and what is the relationship in terms of their degree of openness towards words of this language. The present study was conducted on 70 participants with the aim of analyzing the way in which the use of phrases borrowed from the English language can produce a division of the employee population according to the professional environment in which the employee works. The approach is quantitative, based on a questionnaire that it is based on thematic questions and socio-demographic variables. The questionnaire was applied in physical format to the employees of the two categories. The sample is one of convenience and the results only represent a general picture of the situation, without being generalizable to the entire population of employees.